Гнездование чомги (Podiceps cristatus L.) на Молочном лимане Азовского моря - Филонов, К.П.; Лысенко, В.И.; Рева, П.П. (Вестник зоологии, 1970)
Сообщается, что чомга, прежде гнездившаяся на Молочном лимане лишь в его верховьях в зарослях тростника, с 1963 г. начала гнездиться в несвойственных ей стациях — вблизи открытых островов лимана. Приводятся данные о численности колоний чомги, величине кладок, размерах яиц, длительности периода гнездования. Podiceps crist at us L. till 1963 nested in Molochny estuary of the Sea of Azov only in
its upper part, in reed thickets in stations typical of it. Usually nesting birds numbered
here 150 pairs. Since 1963 Podiceps cristatus L. have begun nesting in stations unusual
for them — near the open islands of the estuary. The most numerous colony was on Dolgy
island: 112 nests in 1965, 165 — in 1967 and 119 — in 1968. These nests made of Zostera
sp. were stable in keeping to shallow water very firmly. The quantity of oviposition varies
within the limits of 1—7 eggs, at Ian average (n = 97) 4±0.1 4 eggs; an average size of
the egg s is 54.4x36.2 mm (n = 18) in 1967 and 56.0 x 34.9 mm (n = 19) — in 1968. The
period of nesting is prolonged: the latest ovipositions were met from the first ten day of
May till the middle of June, and nestlings — from the middle of May till the middle of
July.